Analisis Aktivitas Belajar Siswa Pada Pembelajaran Geografi Materi Kondisi Wilayah dan Posisi Strategis Indonesia Sebagai Poros Maritim Dunia - Dedek Tri Yohanda; Nofrion nofrion (JURNAL BUANA, 2019)
ABSTRACT This article was written to analyze student learning activities, constraints faced by teachers and efforts made by teachers in developing student learning activities in learning Geography of material conditions and Indonesia's strategic position as the world's maritime axis. This type of research uses quantitative descriptive methods. The population in this study were all students of class XI IPS. Sampling using Purposive Sampling technique with selected sample results are class XI IPS 3 and class XI IPS 4. The results of this study indicate that learning activities in class XI IPS 3 and XI IPS 4 SMAN 1 Batang Anai material on regional conditions and Indonesia's strategic position as the axis world maritime is still categorized as MOTS (Middle Order Thinking Skill). Based on the research results obtained 23% - 35.3% of students in class XI IPS 3 and 24% - 33% of students in class XI IPS 4 who carry out basic learning activities (ABD) as a whole with enthusiasm and consistency, and there are 9% - 35% of class XI IPS 3 students and 3% -30% of class XI IPS 4 who carry out advanced learning activities (ABL) as a whole are enthusiastic and consistent.